2008
DOI: 10.1021/es800200g
|View full text |Cite
|
Sign up to set email alerts
|

NOxRemoval from Simulated Flue Gas by Chemical Absorption−Biological Reduction Integrated Approach in a Biofilter

Abstract: A chemical absorption-biological reduction integrated approach, which combines the advantages of both the chemical and biological technologies, is employed to achieve the removal of nitrogen monoxide (NO) from the simulated flue gas. The biological reduction of NO to nitrogen gas (N2) and regeneration of the absorbent Fe(II)EDTA (EDTA:ethylenediaminetetraacetate) take place under thermophilic conditions (50 +/- 0.5 degrees C). The performance of a laboratory-scale biofilter was investigated for treating NO(x) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 19 publications
(37 reference statements)
2
50
0
Order By: Relevance
“…However, our previous work showed a low NO elimination capacity in the biofilter which could result in a large size of the bioreactor and hence increase the cost of NO removal from flue gas. Experimental results showed that, compared with our previous work (Zhang et al 2008), this biofilter packed with a packing material possessing larger specific surface area (1200 m 2 m −3 ) exhibited a higher NO removal efficiency and capacity. For example, at a NO loading rate of 25.9 g NO m −3 h −1 , an increase of the surface area of the packing material from 325 to 1200 m 2 m −3 resulted in an increase of NO removal capacity by 30 % compared to our NO concentration, mg m -3 NO removal efficiency, % previous work (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…However, our previous work showed a low NO elimination capacity in the biofilter which could result in a large size of the bioreactor and hence increase the cost of NO removal from flue gas. Experimental results showed that, compared with our previous work (Zhang et al 2008), this biofilter packed with a packing material possessing larger specific surface area (1200 m 2 m −3 ) exhibited a higher NO removal efficiency and capacity. For example, at a NO loading rate of 25.9 g NO m −3 h −1 , an increase of the surface area of the packing material from 325 to 1200 m 2 m −3 resulted in an increase of NO removal capacity by 30 % compared to our NO concentration, mg m -3 NO removal efficiency, % previous work (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 56%
“…The feasibility of NO x removal from the flue gas by chemical absorption-biological reduction integrated process in a biofilter was demonstrated in our previous work (Zhang et al 2008). However, our previous work showed a low NO elimination capacity in the biofilter which could result in a large size of the bioreactor and hence increase the cost of NO removal from flue gas.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations